A Medicinal Chemistry-Driven Approach Identified the Sterol Isomerase EBP as the Molecular Target of TASIN Colorectal Cancer Toxins - Theodoropoulos, Panayotis C. (J Am Chem Soc, 2020)
TASIN (Truncated APC-Selective Inhibitors) compounds are selectively toxic to colorectal cancer cells with APC mutations, although their mechanism of action remains unknown. Here, we found that TASINs inhibit three enzymes in the post-squalene cholesterol biosynthetic pathway including EBP, DHCR7, and DHCR24. Even though all three of these enzymes are required for cholesterol biosynthesis, only inhibition of the most upstream enzyme, EBP, led to cancer cell death via depletion of downstream sterols, an observation that was confirmed by genetic silencing of EBP. Pharmacologic inhibition or genetic silencing of either DHCR7 or DHCR24 had no impact on cell viability. By using photo-affinity probes to generate a relationship between chemical structure and probe competition, we identified compounds that selectively inhibit either EBP or DHCR7. These studies identify EBP, but not downstream enzymes in the cholesterol biosynthetic pathway, as a target in APC mutant colorectal cancer and also have implications for the clinical development of highly selective EBP inhibitors.